Co Detector: Covid detector device / Mohd Danish Mohd Faizal - Mohd Faizal, Mohd Danish (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
We all suffer with the existence of covid-19 virus since 2019. With that in mind, I intend to develop a device that can help lower the risk of covid-19 virus infection using the technology advantages we already have. As we know that school will be reopened soon. In that purpose, I chose school as my target location to reduce the chances of the covid-19 virus to spread widely. Many adolescents will return to school inadvertently and become infected with the Covid 19 virus without us noticing. This sparked the idea for me to build a solution that may help kids avoid catching the covid virus 19. After some study, I came up with the idea of creating a Co Detector, which is a gadget that can determine whether a student has been exposed to covid or has close family members who have been exposed to covid or not. Techme Co Detector is a device which is used to detect the status of each student who comes to school whether good or bad. It also has a simple operation and more eco-friendly. Co Detector is made from sustainable material which is plastic and leather on the outside part . Co Detector also uses sustainable energy which is solar energy . The benefits of Solar energy: 1 )Rechargeable 2)Renewable source 3)Emissions free 4) No chemicals needed 5)Long lifespan 6)Clean Energy